2003
DOI: 10.3168/jds.s0022-0302(03)73914-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of LPS-Binding Protein in Bovine Blood and Milk Following Bacterial Lipopolysaccharide Challenge

Abstract: Several species of gram-negative bacteria, including Escherichia coli, Klebsiella pneumoniae, and various species of Enterobacter, are common mastitis pathogens. All of these bacteria are characterized by the presence of endotoxin or lipopolysaccharide (LPS) in their outer membrane. The bovine mammary gland is highly sensitive to LPS, and LPS has been implicated, in part, in the pathogenesis of gram-negative mastitis. Recognition of LPS is a key event in the innate immune response to gram-negative infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 75 publications
9
112
1
1
Order By: Relevance
“…The increases in milk BSA concentrations, which mainly reflect increased permeability of the endothelial and epithelial barriers, were of low amplitude compared to endotoxin-induced mastitis: 3 to 10 mg/mL after intrammammary infusion of E. coli endotoxin [2,46], compared to less than 1 mg/mL in this study. It is noteworthy that 10 g LTA induced a change in BSA similar to that seen in experimental subclinical mastitis [43] and 100 g LTA induced a change in BSA similar to that seen in clinical S. aureus mastitis [4].…”
Section: Discussioncontrasting
confidence: 60%
“…The increases in milk BSA concentrations, which mainly reflect increased permeability of the endothelial and epithelial barriers, were of low amplitude compared to endotoxin-induced mastitis: 3 to 10 mg/mL after intrammammary infusion of E. coli endotoxin [2,46], compared to less than 1 mg/mL in this study. It is noteworthy that 10 g LTA induced a change in BSA similar to that seen in experimental subclinical mastitis [43] and 100 g LTA induced a change in BSA similar to that seen in clinical S. aureus mastitis [4].…”
Section: Discussioncontrasting
confidence: 60%
“…The increase paralleled previously reported increases in sCD14 in milk whey in response to LPS using commercially available mAb [3]. In that study, it was also shown that increases in milk neutrophil counts preceded the increase in sCD14.…”
Section: Discussionsupporting
confidence: 89%
“…Membrane CD14 is important for conferring sensitive cellular responses to LPS. LPS induction of cytokine release, particularly TNF-α and IL-1, is probably the central most important event in initiating the acute-phase response to infection [3]. LPS stimulates the cells by ligating specific membrane receptors like CD14 that are important for cytokine release.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the clinical cases of bovine mastitis that occur annually, 40% are caused by Gramnegative bacteria [16,46]. A key component of the host immune response to Gramnegative infections is the upregulation of cytokine production [5,39,40]. Most studies have focused on the immunomodulation changes affected by bovine mononuclear cells, and only a few have been conducted on immunomodulation changes affected by bovine PMN.…”
Section: Introductionmentioning
confidence: 99%
“…PMN recruitment to the site of infection is further mediated by the upregulation of the chemoattractant IL-8 [40]. The concentration of IL-8 increases rapidly after experimental challenge with either LPS or Escherichia coli, and precedes the increase in milk somatic cells [5,7]. IL-12, which is produced by macrophages and B-lymphocytes in response to LPS, plays a key role in the initiation of both innate and antibodyspecific pro-inflammatory immunity [44].…”
Section: Introductionmentioning
confidence: 99%